2017
DOI: 10.1111/trf.13993
|View full text |Cite
|
Sign up to set email alerts
|

Amustaline (S‐303) treatment inactivates high levels of Zika virus in red blood cell components

Abstract: BACKGROUND:The potential for Zika virus (ZIKV) transfusion-transmission (TT) has been demonstrated in French Polynesia and Brazil. Pathogen inactivation (PI) of blood products is a proactive strategy to inactivate TT pathogens including arboviruses. Inactivation of West Nile, dengue, Zika, and chikungunya viruses was previously demonstrated by photochemical treatment with amotosalen and ultraviolet A (UVA) illumination. In this study, we evaluated ZIKV inactivation in red blood cell (RBC) components by a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 53 publications
(103 reference statements)
4
37
0
1
Order By: Relevance
“…Our previous studies illustrated the ability of the amotosalen/UVA system to inactivate greater than 6.4 log 10 TCID 50 /mL in platelets in plasma-PAS, equating to greater than 8.7 log 10 GEq/mL of CHIKV RNA and greater than or equal to 7.6 log 10 TCID 50 / mL in plasma, corresponding to greater than 9.9 log 10 GEq/mL of CHIKV RNA (Table 3). 33 These results are consistent with similar correlations identified in other arboviruses, such as Zika, 36 dengue 40 and West Nile viruses, 41 in which the genomic viral loads correspond from 100-fold to 1000-fold the infectivity titers observed in the same samples, as determined by comparing infectivity titers measured by cell culture assays with viral loads measured by nucleic acid amplification assays. With CHIKV and other arboviruses emerging and reemerging in various geographies, the safety of the blood supply is at stake in both endemic and nonendemic areas.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our previous studies illustrated the ability of the amotosalen/UVA system to inactivate greater than 6.4 log 10 TCID 50 /mL in platelets in plasma-PAS, equating to greater than 8.7 log 10 GEq/mL of CHIKV RNA and greater than or equal to 7.6 log 10 TCID 50 / mL in plasma, corresponding to greater than 9.9 log 10 GEq/mL of CHIKV RNA (Table 3). 33 These results are consistent with similar correlations identified in other arboviruses, such as Zika, 36 dengue 40 and West Nile viruses, 41 in which the genomic viral loads correspond from 100-fold to 1000-fold the infectivity titers observed in the same samples, as determined by comparing infectivity titers measured by cell culture assays with viral loads measured by nucleic acid amplification assays. With CHIKV and other arboviruses emerging and reemerging in various geographies, the safety of the blood supply is at stake in both endemic and nonendemic areas.…”
Section: Discussionsupporting
confidence: 88%
“…B). The RBC units were treated with amustaline/GSH, as described by Laughhunn and colleagues . Two preinactivation samples were taken from all units: one was frozen immediately after inoculation with CHIKV and dosing with GSH, and the other was allowed to incubate at room temperature for 3 hours to mirror the treated RBC units.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inactivation of ZIKV with the INTERCEPT PI system in PLTs suspended in 35 or 100% plasma resulted in more than 4.1 log reduction in viral infectivity, whereas for plasma, more than 6.46 log reduction was achieved . Laughhunn and colleagues have also shown the capacity of a novel inactivation process to reduce ZIKV infectivity in red blood cells (RBCs) by more than 4.3 log, whereby components are treated with amustaline (S‐303) and glutathione without the need for illumination. Variable viral loads have been detected in ZIKV‐infected blood donors, and not all recipients of ZIKV‐infected blood develop symptoms indicative of disease after transfusion .…”
Section: Discussionmentioning
confidence: 99%
“…With the completion of this study, it has now been formally demonstrated that nucleic acid-targeted PI methodologies effectively inactivate ZIKV in all three blood components: in plasma (>6.57 log 10 TCID 50 , >10.25 log 10-GEq/mL) 28 and platelets (>4.42 log 10 TCID 50 , >7.46 log 10 GEq/mL) using amotosalen/UVA and in red blood cells (>5.99 log 10 TCID 50 , 7.75 log 10 GEq/mL) using amustaline/ glutathione 31 (Table 6). In addition, similar levels of inactivation have been recorded for other common arboviruses, such as CHIKV, DENV, and WNV (Table 6).…”
mentioning
confidence: 99%